Delayed Symptom Onset Following Pediatric Sport-Related Concussion - Olson, Ashley; Ellis, Michael J.; Selci, Erin; Russell, Kelly (Frontiers in Neurology, 2020)
Objective: 1) To examine the prevalence of delayed symptom onset (DSO) among pediatric sport-related concussion (SRC) patients as well as the effect of symptom onset on initial symptom severity, length of recovery, and development of delayed recovery; 2) to evaluate the impact of symptom onset on sideline management. Methods: We conducted a prospective study of pediatric SRC patients (<20 years of age) evaluated at a multi-disciplinary concussion program. Patients underwent initial medical assessment by a single neurosurgeon and a structured interview by a research assistant. Patients were classified as experiencing early symptom onset (symptom onset <15 minutes from the time of the suspected injury; ESO) or DSO (≥15 minutes from the time of the suspected injury). Results: A total of 144 SRC patients (61.1% male; mean age 14.6 years, SD 1.8) evaluated a median of 5.0 days (IQR 4.0, 9.0) post-injury were included in the study. Among these patients, 120 (83.3%) reported experiencing ESO while 24 (16.7%) experienced DSO following injury. Among those that experienced DSO the median length of time from the suspected injury to symptom onset was 60.0 minutes (IQR 20.0, 720.0). No risk factors for the development of DSO were identified. No significant differences were observed in symptom severity at initial medical assessment (median Post-Concussion Symptom Scale score 20.0 vs 18.0, p=0.35), length of physician-document clinical recovery (median 22.0 vs. 24.0 days; p=0.46) or the proportion of those who developed delayed physician-documented clinical recovery (34.4% vs 42.1%, p=0.52) among patients with ESO or DSO. Patients who reported experiencing ESO were significantly more likely to be immediately removed from play at the time of their suspected injury compared to those who experienced DSO (71.6% vs 29.2%; p<0.0001). Conclusions: This study suggests that an important proportion of children and adolescents who sustain an acute SRC experience DSO. DSO is associated with lower rates of immediate removal from play at the time of suspected injury. These preliminary findings highlight the need for improved sport stakeholder concussion education and standardized concussion protocols that mandate the immediate and permanent removal of all youth with a suspected concussion until they undergo medical assessment.